Prognostic Value of Programmed Electrical Stimulation in Brugada Syndrome. (August 2015) - Sieira, Juan; Conte, Giulio; Ciconte, Giuseppe; de Asmundis, Carlo; Chierchia, Gian-Battista; Baltogiannis, Giannis; Di Giovanni, Giacomo; Saitoh, Yukio; Irfan, Ghazala; Casado-Arroyo, Ruben; Juliá, Justo; La Meir, Mark; et al.
<x xml:space="preserve">Abstract</x> Background— The prognostic value of electrophysiological investigations in individuals with Brugada syndrome remains controversial. Different groups have published contradictory data. Long-term follow-up is needed to clarify this issue. Methods and Results— Patients presenting with spontaneous or drug-induced Brugada type I ECG and in whom programmed electric stimulation was performed at our institution were considered eligible for this study. A total of 403 consecutive patients (235 males, 58.2%; mean age, 43.2±16.2 years) were included. Ventricular arrhythmias during programmed electric stimulation were induced in 73 (18.1%) patients. After a mean follow-up time of 74.3±57.3 months (median 57.3), 25 arrhythmic events occurred (16 in the inducible group and 9 in the noninducible). Ventricular arrhythmias inducibility presented a hazard ratio for events of 8.3 (95% confidence interval, 3.6–19.4), P<0.01. Conclusions— Programmed ventricular stimulation of the heart is a good predictor of outcome in individuals with Brugada syndrome. It might be of special value to guide further management when performed in asymptomatic individuals. The overall accuracy of the test makes it a suitable screening tool to reassure noninducible asymptomatic individuals